2015
DOI: 10.14689/ejer.2015.60.7
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Social Support, Depression and Life Satisfaction as the Predictor of the Resilience of Secondary School Students: The Case of Burdur

Abstract: Problem statement: It has been observed that there are a limited number of studies on the resilience of primary and secondary school students in Turkey. However, it is acknowledged that secondary school students with difficult conditions of life also have to cope with rapid physical, psychological and social changes brought about by adolescence. For this reason, conducting research on the resilience characteristics of students within this age range would be an opportunity to enable them to acquire the abilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
16
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 28 publications
7
16
0
7
Order By: Relevance
“…In the present study, all the measured dimensions of social support were positively associated with resilience, consistent with previous studies [67,68]. If properly used, social support is an important resource for individual coping and health [69].…”
Section: Plos Onesupporting
confidence: 92%
“…In the present study, all the measured dimensions of social support were positively associated with resilience, consistent with previous studies [67,68]. If properly used, social support is an important resource for individual coping and health [69].…”
Section: Plos Onesupporting
confidence: 92%
“…Literatürde ulaşılan ve baş etme becerisini (coping) konu alan araştırmaların (Malkoç ve Yalçın, 2015) Bu noktada farklı kişilik özelliklerinin ve de farklı değişkenlerin yılmazlıkla ilişkisini ve de yılmazlığı yordama düzeyini inceleyen araştırmalara duyulan ihtiyaç gündeme gelmektedir. Yılmazlığı yordayan etkenleri konu alan araştırmalara bakıldığında; benlik saygısı (Gökden-Kaya, 2007;Karataş ve Savi-Çakar, 2011), öğrenilmiş güçlülük (Dayıoğlu, 2008), algılanan sosyal destek, algılanan aile desteği (Luthar, Cicchetti ve Becker, 2000;Dayıoğlu, 2008;Baltacı ve Karataş, 2015) gibi değişkenlerin ele alındığı görülmektedir. Araştırmalar özellikle aileden alınan sosyal desteğin bireylerin yılmazlığının önemli bir belirleyicisi olduğuna vurgu yapmaktadır.…”
Section: Tartişma Ve Sonuçunclassified
“…These individuals participate in social changes and activities, they are faithful; many have the ability to extract meaning and benefits from the troubles, traumas and worries in their lives. The existing research has revealed that resilience is associated with problem solving ( Neenan & Dryden, 2012 ); stress and exhaustion ( Hao et al, 2015 ); locus of control ( Dunn & Brody, 2008 ); family support ( White et al, 2008 ); social support ( Nikmanesh & Honakzehi, 2016 ; Şahin Baltacı & Karataş, 2015 ); hope ( Duggal et al, 2016 ); pessimism and positive affectivity ( Tugade & Fredrickson, 2004 ) and life satisfaction ( Akbar et al, 2014 ; Şahin Baltacı & Karataş, 2015 ); depression ( Şahin Baltacı & Karataş, 2015 ), self-esteem and hopelessness ( Karatas & Savi-Çakar, 2011 ), hope and life satisfaction ( Shetty, 2015 ); life satisfaction, stress and social support ( Yang et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%